Effect of mating on mRNA and protein expression of beta nerve growth factor and its receptor, TrKA, in the oviduct of llama (Lama glama). Issue 11 (6th October 2020) - Sari, Luciana M.; Zampini, Renato; Argañaraz, Martin E.; Ratto, Marcelo H.; Apichela, Silvana A.
Abstract: Copulation produces different stimuli in the female reproductive tract in camelids, which lead to ovulation. Expression of β‐nerve growth factor (β‐NGF) and its specific receptor, tropomyosin receptor kinase A (TrKA), was studied comparing the oviductal microenvironment of mated and nonmated llamas. β‐NGF and TrKA were expressed in the llama ampulla, isthmus, and utero‐tubal‐junction (UTJ), and they were mainly colocalized in the apical region of the oviductal mucosa. A TrKA immunosignal was also found in muscle cells and blood vessels, with the highest mark in UTJ muscle cells of copulated females. Both β‐NGF and TrKA transcripts were expressed in the three oviductal segments. Relative TrKA abundance did not differ between mated and nonmated females, but relative β‐NGF abundance was higher in the UTJ of copulated females ( p  < .05). β‐NGF might not be secreted into the oviductal fluid (OF) since the protein was not found in the OF of mated or nonmated females. Therefore, it can be concluded that the llama oviduct expresses the β‐NGF/TrKA system and that an increase in β‐NGF gene expression in the UTJ 24 h after copulation along with an increase in TrKA protein expression may indicate an important role in the gamete transport and fertilization process in llamas. Graphical abstract: Expression of β‐nerve growth factor (β‐NGF) and its specific receptor, tropomyosin receptor kinase A (TrKA), was studied comparing the oviductal microenvironment of mated and nonmated llamas. The llama oviduct expresses the β‐NGF/TrKA system. We observed an increase in β‐NGF gene expression in the utero‐tubal junction 24 h after copulation along with an increase in TrKA protein expression that may indicate an important role in the gamete transport and fertilization process in llamas.